Rhetorical analysis of the phenomenon of seasons of the year in school book: a comparative study through social representations (Revista Contexto & Educação, 2023)
The aim of this study was to investigate whether the Social Representations regarding the phenomenon of the seasons of the year, shared by students graduating from Elementary School, result from the rhetoric used in textbooks adopted by the educational institution. The investigation was developed from the exploration of textbooks, used by subjects who share this social representation, during their school career in Elementary School. The rhetorical analysis of textbooks shows evidence that the arguments listed by the authors are not enough to persuade their readers, in a manner consistent with the learning expectations of the Education Curriculum Guidelines, the official education document that guided the preparation of the works. However, the comparative study shows divergence between the social representations shared by these students and the existing content in textbooks, regarding the astronomical in question. This result is consistent with the basic foundations for the construction of learning, in a constructivist perspective. After all, if an instructional material will not provide conditions for associating new information with the student's idiosyncratic knowledge, there will be no learning.